This study is aim to analyze the expost (2001-2004) and exante (2007-2010) impacts of industrial relation issues on Indonesian economy in the era of regional autonomy. To reach this objective, a simultaneous equations model containing 34 stuctural equations and 18 identity equations is constructed. Time series 1980-2004 data was used in this study and model was estimated by 2SLS Method, SYSLIN Procedure. Historical and forcasting simulation used the SIMNLIN Procedure. Estimated parame - Evi Lisna; Bonar M. Sinaga; Sjafri Mangkuprawira; Hermanto Siregar (Forum Pasca Sarjana, 2010)
This study is aim to analyze the expost (2001-2004) and exante (2007-2010) impacts of industrial relation issues on Indonesian economy in the era of regional autonomy.  To reach this objective, a simultaneous equations model containing 34 stuctural equations  and 18  identity  equations is  constructed.  Time  series   1980-2004 data was used in this study and model was estimated by 2SLS Method, SYSLIN Procedure.  Historical and forcasting simulation used the SIMNLIN Procedure.  Estimated parameters of the model suggest that an increase of minimum wage policy, emergence of labour union and strike cases affect significantly on investment, agregate supply, unemployment and inflation.  Results of the simulations analysis indicate that solving industrial relation issues is potential to increase investment and agregate supply as well as to decrease unemployment and inflation in 2007-2010.   Key words: industrial relation issues, economy, regional autonomy